Profitability Underperformance and Benchmark Gaps: Evidence from PT Japfa Comfeed Indonesia Tbk (2019–2023) - Zalukhu, Lefina Kristiani; Siswanto, Siswanto; Sinaga, Irwan Nopian (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: This study aims to assess the financial performance of PT. Japfa Comfeed Indonesia, Tbk. during the period 2019–2023 using profitability ratios, namely Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), and Gross Profit Margin (GPM). The research seeks to determine the extent to which the company’s profitability metrics align with established industry benchmarks. Materials and methods: A qualitative descriptive research design was employed utilizing secondary data obtained from the published annual financial statements of PT. Japfa Comfeed Indonesia, Tbk. for the fiscal years 2019–2023. Financial data were sourced from the Indonesia Stock Exchange (IDX) database. Profitability ratios were calculated using standard formulas and subsequently compared against industry average standards. Descriptive statistical analysis, including trend analysis and mean computation, was applied to interpret the data. Results: The findings reveal that all four profitability ratios fell substantially below industry average standards throughout the observation period. The average NPM was 3% (industry standard: 20%), ROA averaged 4% (industry standard: 30%), ROE averaged 11% (industry standard: 40%), and GPM averaged 4% (industry standard: 40%). A declining trend was observed across most indicators from 2021 to 2023, suggesting deteriorating profitability performance. Conclusions: The financial performance of PT. Japfa Comfeed Indonesia, Tbk. based on profitability ratios is considered unsatisfactory over the 2019–2023 period, as all metrics remain significantly below industry benchmarks. The company must implement strategic measures to optimize asset utilization, improve cost management, and enhance capital efficiency to achieve competitive profitability standards. Future research should incorporate additional financial metrics and employ comparative analysis with peer companies.